86.9k views
1 vote
7(n - 7) = 3(2n + 3)

1 Answer

1 vote

Answer: n=58

Explanation:

7(n-7)=3(2n+3)

We move all terms to the left:

7(n-7)-(3(2n+3))=0

We multiply parentheses

7n-(3(2n+3))-49=0

We calculate terms in parentheses: -(3(2n+3)), so:

3(2n+3)

We multiply parentheses

6n+9

Back to the equation:

-(6n+9)

We get rid of parentheses

7n-6n-9-49=0

We add all the numbers together, and all the variables

n-58=0

We move all terms containing n to the left, all other terms to the right

n=58

User Semur Nabiev
by
4.3k points